Comparative Physicochemical and Pharmacotechnical Evaluation of Three Topical Gel-Cream Formulations - Ramona Pârvănescu; Cristina Trandafirescu; Adina Magdalena Musuc; Emma Adriana Ozon; Daniela C. Culita; Raul-Augustin Mitran; Cristina-Ionela Stănciulescu; Codruța Șoica (Gels, 2025)
In the context of modern dermocosmetic development, multifunctional topical gel-cream formulations must be efficient for both therapeutic efficacy and cosmetic applications. This study presents a comparative physicochemical and pharmacotechnical analysis of three topical gel-cream formulations developed by Brand Chanand®: Acne Control Cleanser (ACC), Acne Face Cream (AFC), and Gentle Cream Cleanser Serum Control, Regenerating, Hydrating, Calming (IRC). Each formulation is enriched with a specific blend of bioactive compounds, including botanical oils, vitamins, and proteins, designed to treat acne, to support skin regeneration, and to maintain the skin barrier. A multidisciplinary approach was used, including Fourier Transform Infrared Spectroscopy with Attenuated Total Reflectance (FTIR-ATR), differential scanning calorimetry (DSC), rheological evaluation, pH and density determination, spreadability analysis, and oxidative stability testing to evaluate the products. Antioxidant capacity was assessed through multiple in vitro assays. The results demonstrated that all three gel-cream formulations exhibit pseudoplastic rheological behaviour, suitable for topical application. AFC showed the highest oxidative stability and antioxidant activity, while IRC presented superior spreadability and cosmetic efficacy, likely due to its complex composition. ACC displayed faster absorption and was ideal for targeted use on oily or acne-prone skin. The differences observed in the stability and performance suggest that the ingredient synergy, base composition, and solubility profiles show notable variations in dermato-cosmetic formulations. These findings highlight the formulation–performance relationship in topical gel-cream formulations and support the development of new cosmetic products tailored for sensitive and acne-prone skin.